A comparative study of astigmatism following manual small incision cataract surgery and conventional extracapsular cataract extraction at a tertiary centre in northern india - Khanday, Sajad; Maqbool Wani, Raashid; Ramzan, Rahila; Runyal, Farooq (International Journal of Medical Research and Review, 2015)
Objective: To compare the surgically induced astigmatism following two different techniques of cataract surgery-manual SICS (Small Incision Cataract Surgery) and standard ECCE (Extra-Capsular Cataract Extraction). Materials and Methods: Subjects consisted of patients, aged 10-80 years, from both sexes and divided into two groups of 100 each (one eye per patient). One group was operated with manual SICS and the other with standard ECCE technique. Results: The mean surgically induced astigmatism (SIA) in the SICS group during the sixth week postoperative follow up was found to be 0.66D ± 0.60 SD (Standard Deviation) compared to 2.25D ± 1.23 SD in the ECCE group. At 6th week follow up, no patient in the SICS group had SIA more than 3D whereas in the ECCE group 30% of the patients had astigmatism >3 D. The induced astigmatism between the two groups had a p-value of <0.001 which is highly significant. Conclusions: It is concluded that SICS induces less surgically induced astigmatism, less inflammation, less complications influencing the overall visual prognosis and quick stabilization of refraction, hence providing better and rapid visual rehabilitation in the postoperative period as compared to the patients in the ECCE group.